The Influence of Inflation, Sukuk, and Mutual Funds On The Indonesian Sharia Stock Index (ISSI) - Octavia, Melanie; Natasha; Amalia, Sabrina; Purba, Seprianto; Silitonga, Claudia Jeremia; Chrisna, Heriyati (Indonesian Journal Publisher, 2024)
From 2018 - 2023 there were fluctuations in the value of the Islamic Stock Index. This study uses associative tests to analyze and obtain empirical evidence, whether inflation, sukuk and mutual funds have a significant effect on the Indonesian Islamic stock index. The data used is secondary data taken from the official website, namely www.ojk.go.id, and www.bps.go.id. The results of this study, individually sukuk has a negative and insignificant effect on the Indonesian Islamic stock index, then individually sukuk and mutual funds have a positive and significant effect on the Indonesian Islamic stock index. But simultaneously the three independent variables have a significant effect on the Indonesian Islamic stock index with an influence value of 69.7%, where the other 30.3% value is influenced by other variables not included by researchers.